A new species and new record of the leaf-mining genus Dactylotula Cockerell (Lepidoptera: Gelechiidae) from China - Yang, Huiduo; Teng, Kaijian; Liu, Tengteng (Zootaxa, 2023)
Until recently, only two species of Dactylotula Cockerell, 1888 have been known. Dactylotula kinkerella (Snellen, 1876), feeding on Calamagrostis arenaria (L.) Roth (Poaceae), is distributed in Europe and the Asian part of Russia, while D. altithermella (Walsingham, 1903) was only recorded in Europe with host plant unknown. Here, we report Dactylotula for the first time in China represented by a new leaf-mining species described herein as D. phragmitella, sp. n., feeding on Phragmites australis (Cav.) Steud. (Poaceae). Most of the specimens were collected in the Yellow River Delta. Photos of the adult, wing venation, male and female genitalia, host plant, leaf mines and parasitoid wasps of the new species are provided. Additionally, DNA barcodes of the new species are provided and discussed along sequences of the other two congeneric species.